(untitled) (Applied Biological Research, 2014)
Cinnamomum tamala Nees., a valuable spice-yielding plant of Himalaya, is vulnerable in its natural habitat due to its over-collection for spice and medicinal purpose. In the present study, a successful attempt was made for in vitro shoot bud induction from cotyledons and plant regeneration. The culturedcotyledons of 10-11wk after flowering induced meristematic response within 4-5 wk of culture where 43% explants responded positivelyonMSmediumfortifiedwith 3% sucrose, polyvinyl pyrollidone (100mgL-1) and 6 µM benzyl adenine wherein 5-6 shoot buds developed cotyledon-1.Themicro-shoots/shoot buds,developedon initiation medium, were maintained on MS medium fortified with 3% sucrose and 3 µM kinetin where shoot buds converted into plantlets and supported culture proliferation. Shoots (4 cm long) with fully open leaves were rooted by maintaining on MS medium enriched with 3 µM α-naphthalene acetic acid where 5-6 roots developed per micro-shoot. The rooted plants were transferred to potting mix and maintained in agro-shade ca75% shading where 65% transplants survived after two months of transfer.